2019
DOI: 10.1097/scs.0000000000005916
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Assessment of Orthognathic Surgery Patients

Abstract: Objectives: To retrospectively assess malocclusions, skeletal relationships and the functional needs of orthognathic patients treated in a University teaching hospital. Subjects and methods: This study used clinical records of 100 consecutive patients [51 female, 49 males, mean (SD) age =21.5 (2.71) years] who had orthognathic surgery in a Shahid Beheshti University of Medical Sciences affiliated hospital (9/2014–7/2017). Malocclusion type (incisor clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
2
10
0
1
Order By: Relevance
“…A limitation of this study is that only the facial profile silhouettes were evaluated, and both treatments, camouflage orthodontics and orthognathic surgery, change the frontal view of the patient. However, in Class III patients, the facial profile discrepancy is usually the most esthetic impairment and the main complaint of patients [ 9 , 10 ]. This way, even with this limitation, we can speculate that changes in the facial profile in both treatment approaches, even if one is only a surgical simulation, will reflect in similar changes in the frontal view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study is that only the facial profile silhouettes were evaluated, and both treatments, camouflage orthodontics and orthognathic surgery, change the frontal view of the patient. However, in Class III patients, the facial profile discrepancy is usually the most esthetic impairment and the main complaint of patients [ 9 , 10 ]. This way, even with this limitation, we can speculate that changes in the facial profile in both treatment approaches, even if one is only a surgical simulation, will reflect in similar changes in the frontal view.…”
Section: Discussionmentioning
confidence: 99%
“…According to the IOFTN, the Class III patients present a higher functional need for orthognathic surgery than other malocclusions [ 8 , 9 ]. Most cases that are treated with orthognathic surgery in different countries present initially Class III malocclusion [ 8 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with malocclusion are affected predominantly and have been investigated in several studies [4][5][6]. Orthognathic patients with class II and III malocclusion showed major variations of the temporomandibular joint (TMJ) in size and shape [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies described a variable prevalence of skeletal jaw relationships among Iranian children, all reporting the lowest level for skeletal Class III. The prevalence of dental malocclusion also reported by Borzabadi-Farahani and Akbari in Iranian children that they showed the most prevalent malocclusion was Cl I followed by Cl II, and the lowest was Cl III, although, the most prevalent malocclusion among the patients in need of orthognathic surgery was the Cl III malocclusion (45.6%) 18,19,20,27 . The variability among the different studies may be due to the varying methods and indices used to assess, differing sample selection, examiner subjectivity, and specific objectives.…”
Section: Discussionmentioning
confidence: 54%
“…Eslamipour et al found the prevalence of 5%, 52%, and 44% for Class I, II, and III sagittal skeletal pattern, respectively, among the patients who needed orthognathic surgery 19 . Eslamian et al reported 68% and 32% Class III and II sagittal skeletal relationship, respectively among the patients who had orthognathic surgery 20 .…”
Section: Discussionmentioning
confidence: 98%